2013
DOI: 10.1021/es4036072
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Degradation of Deepwater Horizon Spilled Oil by Indigenous Microbial Communities in Louisiana Saltmarsh Sediments

Abstract: The Deepwater Horizon oil spill led to the severe contamination of coastal environments in the Gulf of Mexico. A previous study detailed coastal saltmarsh erosion and recovery in a number of oil-impacted and nonimpacted reference sites in Barataria Bay, Louisiana over the first 18 months after the spill. Concentrations of alkanes and polyaromatic hydrocarbons (PAHs) at oil-impacted sites significantly decreased over this time period. Here, a combination of DNA, lipid, and isotopic approaches confirm that micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
78
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 91 publications
(164 reference statements)
4
78
3
Order By: Relevance
“…Total petroleum hydrocarbons, and aliphatic and aromatic compounds were highly weathered and depleted within the first few months to years after oil from the DWH spill came ashore onto beaches (Hayworth et al, 2015) and wetlands (Mahmoudi et al, 2013;Atlas et al, 2015). Whereas alkanes and low molecular weight PAHs were largely depleted in coastal sediments, high molecular weight PAHs (e.g., chrysene) persisted and could remain for many years.…”
Section: Pelagicola Litoralis Strain Cl-es2mentioning
confidence: 99%
See 2 more Smart Citations
“…Total petroleum hydrocarbons, and aliphatic and aromatic compounds were highly weathered and depleted within the first few months to years after oil from the DWH spill came ashore onto beaches (Hayworth et al, 2015) and wetlands (Mahmoudi et al, 2013;Atlas et al, 2015). Whereas alkanes and low molecular weight PAHs were largely depleted in coastal sediments, high molecular weight PAHs (e.g., chrysene) persisted and could remain for many years.…”
Section: Pelagicola Litoralis Strain Cl-es2mentioning
confidence: 99%
“…Oil contamination from the DWH spill had a profound impact on the abundance, structure, and metabolic potential of sedimentary microbial communities along beaches (Kostka et al, 2011) and marshes (Mahmoudi et al, 2013;Atlas et al, 2015) of the northern Gulf Coast. A time series study conducted at Pensacola Beach, Florida, where total petroleum hydrocarbons reached 11,000 mg kg -1 , revealed a bloom of bacteria during the first four months after oil came ashore, with microbial abundance in oiled sands 10 to 10,000 times that of clean sands (Kostka et al, 2011).…”
Section: Pelagicola Litoralis Strain Cl-es2mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that between 4.2 and 4.9 million barrels of oil were released making it the largest accidental oil spill in history. [1][2][3] Numerous studies have examined the fate and impact of released Macondo oil within the plume [4][5][6][7][8] , on the surface of the Gulf 5,9,10 , buried in ocean sediments (either directly or as marine snow) 6,10 , in marshes [11][12][13][14] , and on beaches. 10,12,14-19 Not surprisingly, the environmental fate of the oil was influenced by many well documented weathering processes.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…Accordingly, application of improved indigenous bacterial communities is thought to be a potential bioremediation strategy to overcome pollution problems associated with local river . Mahmoudi et al (2013) reported that spilled oil can be rapidly degraded by the indigenous bacterial community of saltmarsh sediment, suggesting that these of microorganisms have the potential for in situ bioremediation. However, the bacterial communities in river sediment remain largely unexplored owing to complicated environmental stresses and regional bacterial differentiation.…”
Section: Introductionmentioning
confidence: 99%